MiR-34a ameliorates arterial blood flow in rats with lower limb arteriosclerosis obliterans via Sirt1 signaling pathway: MiR-34a in rats with lower limb arteriosclerosis obliterans - Xu, Tuo; Zheng, Changwei; Wu, Yongkang; Chen, Zhengde; Miao, Huilai (Cellular and Molecular Biology, 2024)
In this study, we investigated the impact of microRNA-34a (miR-34a) on lower limb arteriosclerosis obliterans in rats through the Sirtuin 1 (Sirt1) signaling pathway. Thirty-six Sprague-Dawley rats were divided into normal, model, and miR-34a mimics groups. Rats in the normal group were raised normally, while the model group underwent lower limb arteriosclerosis obliterans induction and received saline injections. The miR-34a mimics group also underwent arteriosclerosis obliterans modeling but received miR-34a mimics injections. Immunohistochemistry revealed significantly increased vascular endothelial growth factor (VEGF) expression in both model and miR-34a mimics groups compared to the normal group, with the miR-34a mimics group showing higher levels. Western blotting indicated elevated Sirt1 protein expression in both non-normal groups, with the miR-34a mimics group exhibiting significantly higher levels. Quantitative polymerase chain reaction (qPCR) demonstrated higher levels of miR-34a, VEGF mRNA, and Sirt1 mRNA in the model group compared to the normal group, but significantly lower levels than the miR-34a mimics group. Enzyme-linked immunosorbent assay (ELISA) showed increased VEGF content in the model group compared to the normal group but decreased compared to the miR-34a mimics group. Hemorrheological detection revealed a reduced PU index in both non-normal groups compared to the normal group, with a significant increase in the miR-34a mimics group compared to the model group. Overall, miR-34a upregulation enhanced VEGF expression in rat blood vessels, ameliorating arterial blood flow in lower limb arteriosclerosis obliterans through the Sirt1 signaling pathway.